Lake development and vegetation history in coastal Primor'ye: implications for Holocene climate of the southeastern Russian Far East. (12th December 2020) - Lozhkin, Anatoly V.; Anderson, Patricia M.; Brown, Thomas A.; Grebennikova, Tatiana A.; Korzun, Julia A.; Tsigankova, Valeriya I.
Abstract : Latvia Lake provides one of the few high‐resolution palaeoenvironmental records from southeastern Primor'ye. It traces basin, vegetation and climate histories over the past c.  8.6 ka. The Latvia basin experienced four phases, two of which involved frequent shifts amongst lake, lagoon and bay settings ( c.  8.6–7.0 cal. ka BP and c.  2.1 cal. ka BP–present). A sandbar was present between c.  7.0 and 6.9 cal. ka BP. The longest interval of Latvia basin stability was from c.  6.9–2.1 cal. ka BP when the basin was a lagoon of varying salinities. Quercus ‐broadleaf forests characterized the regional vegetation throughout the past c.  8.6 ka. Variations in thermophilous species (e.g. Juglans, Carpinus, Ulmus, Tilia, Syringa ) and Pinus koraiensis reflect shifts in temperature and moisture during the Middle Holocene. A period of warmest climate occurred c.  8.6–5.1 cal. ka BP with wettest conditions from c.  7.5–4.3 cal. ka BP, although all changes in temperature and precipitation were gradual. The Latvia Lake results indicate that changes in Middle to Late Holocene climates were linked more closely to shifts in the East Asian Summer Monsoon and less so to sea level oscillations. This investigation demonstrates that lakes of coastal Primor'ye can provide reliable palaeovegetation and palaeoclimate records despite their changing depositional environments.